The mannose binding lectin gene influences the severity of chronic liver disease in cystic fibrosis. Issue 5 (1st May 2001) - Gabolde, M; Hubert, D; Guilloud-Bataille, M; Lenaerts, C; Feingold, J; Besmond, C
Abstract : Chronic liver disease is a major complication of cystic fibrosis. Its incidence and severity show marked heterogeneity, even among the homogeneous group of homozygous ΔF508 patients, suggesting that environmental or genetic factors other than the deletion ΔF508 may influence the development of cystic fibrosis related liver disease. We investigated whether the allelic variants of mannose binding lectin, an important protein of the immune system, could be associated with the presence of cirrhosis in a population of 216 homogeneous homozygous ΔF508 patients. Analysis of the data shows that the presence of cirrhosis in cystic fibrosis patients is significantly associated with a mutated mannose binding lectin genotype (homozygous or compound heterozygous for mannose binding lectin variants). The modulating role of mannose binding lectin in the occurrence of cirrhosis in cystic fibrosis could be explained by the fact that hepatotoxic damage from viruses or bacteria might be increased by the immunodeficiency associated with mannose binding lectin variants and might facilitate the degradation of liver status. These data highlight the crucial role of mannose binding lectin in the clinical outcome of cystic fibrosis, as it has recently been shown that the mannose binding lectin gene is a modulating gene of the respiratory involvement in cystic fibrosis patients.